Rethinking Paleolithic Visual Culture throughout immersive technology: The site "Cueva de las Manos" as a virtual "Denkraum" (Patagonia, Argentina) - Gutiérrez de Angelis, Marina (2020)
The discussion about the concepts of cave art and painting settled the basis of the project in the archaeological site of Cueva de las Manos in Argentina. The team use the immersive technology of VR and the 360° video as a methodology to explore visuality understood as a corporal act. Our hypothesis maintains that the concept of ?aesthetic experience? is not exclusively artistic, in its modern sense. The immersive medium allows the users to experience in the Cave, as a Virtual Denkraum, the spatial and cinematic sensoriality of the image, that poses open questions, instead of the need to decode meaning in the pictures.